Funkcje środków wartościujących w polskim dyskursie naukowym XVI wieku - Artur Rejter (Stylistyka, 2020)
The paper concerns the problem of axiology exponents in the Polish academic discourse of the 16th century. The research proved that this kind of exponents refer to different discourse levels, from the topic of the discourse, through the field of science, to metatext. As for language determinants one can distinguish evaluating lexis, modal verbs and style exponents (e.g. comparisons, phraseological constructions, enumera- tions). The analysis shows that the subjective aspect of the texts confirms the initial stage of the Polish academic discourse forming process. Furthermore, the style diversity reflects the discourse state which was then rather practical than theoretical.